Teori BREAK : Gaya Bahasa dalam Lirik Lagu Iwan Fals dan Slank - Sari Putri, Tantry Oktafika (Jurnal Hata Poda, 2022)
Style of language is a form described in the conduct of elections diction, phrases and clauses in a sentence. Either in writing or orally. In the selection of diction are some by the author. For some writers, the choice of diction is very important that the purpose and the intended meaning precisely the reader in mind. The lyrics are considered a work rich in diction metaphors or parables. In this paper have two songwriter and singer who uses song lyrics figurative meaning that the lyrics performed by Iwan Fals and Slank. The method used in this paper is a qualitative method with some additional techniques. Then combined with the theory that includes Base BREAK Discourse, Discourse Relations, Equilibrium Discourse, Discourse Actualization, Sustainability Discourse. The lyrics were created by Iwan Fals selected as the primary discourse containing style figurative language and imagery. While the lyrics Slank used as a secondary discourse that only a few uses language metaphors or parables. As a comparison the lyrics of this song were analyzed based languages or parable uses. Keywords: BREAK Theory, language in style, song